Physicochemical changes on pumpkin/pepper sauces during refrigerated storage - Sosa, Carola Andrea (2012)
Changes in rheological, textural and physicochemical characteristics of pumpkin and red bell pepper sauces prepared in 50:50 and 80:20 proportions were studied for 6 days under refrigerated conditions.Variations in sugar, total carotenoids and antioxidant capacity were determined. The compression forces of sauces decreased by 50% at eighth day of storage and sauces behaved as elastic solids with G values predominating over G values. The storage modulus was less frequency dependent than the loss modulus, giving values of tan d between 0.1 and 0.2, which tends to indicate a weak gel system. No significant changes were observed in the physicochemical parameters, except total antioxidant capacity, which decreased by 50% after 6 days. Microbiological counts showed slight increases or remained invariable in total counts for mesophylic bacteria, yeasts and molds during storage.